Peculiarities of Formation of Innovative Territorial Clusters in Russia - Kurbatov, Vladimir Leonidovich; Khalina, Maria Vasilyevna; Volkova, Svetlana Vladimirovna (International Journal of Economics and Financial Issues, 2016)
The current situation in the Russian economy urges participants of economic processes to search and implement the effective technologies of interaction and management. High saturation of sectoral markets currently does not allow their members to gain competitive advantages only through production technologies. More and more companies choose ways to raise the level of competitiveness through the formation of long-term, trusted relationships with business partners. At the same time, during the formation of such relationships, the organizations and enterprises group together in clusters, thus usually seeking to raise the competitiveness in foreign markets and increase the level of professional competence through intra-cluster allocation of resources. For objective historical reasons (the Russian economy was built out of the market), the development of clusters in Russia is facing serious obstacles. Therefore, the emergence of historically conditioned natural clusters described by Porter is virtually impossible in Russia. However, the cluster approach is very promising: the formation and development of clusters is able to raise the competitiveness and efficiency of the economies of the subjects of the Russian Federation. The formation of the cluster and its prospects depend on many factors, so the risk remains that the cluster will not be able to follow the desired trajectory without state support. This article is devotes to the issues of the application of the cluster approach in the formation of Russian innovative economy in general and the formation and development of innovative territorial clusters in particular. The main problems preventing the effective implementation of the cluster approach have been identified on the basis of the analysis of Russian experience in the formation and development of innovative territorial clusters. Keywords: cluster; cluster policy; innovative development; regions, competitiveness. JEL Classifications: C38, R12, P25